MEMBANGUN SISTEM INFORMASI PARIWISATA KECAMATAN SELOGIRI BERBASIS WEB - pranoto, rudi; susilo, dahlan; Al Haris, Firdhaus Hari Saputro (Gaung Informatika, 2014)
Selogiri sub district is one of tourism destination in Wonogiri district , both local tourism of foreign travelers. tourism destination is divided into three catagories there are general tourism , cultural tourism and culinary tourism. tourism promotions that have been done by departement of tourism in Wonogiri only uses brochures and advertisements.The objective in making this information system is to make a media of tourism promotion in order to know by the public through the website. method of design system uses system design based on object. meanwhile information system is made by using PHP and MySQL as a database. the result of website from the research contains information about tourism in Selogiri subdistrict. information system is tested by using WebQual method. the tested result of show 81,1 %, it means that tourism website of Selogiri subdistrict is stated as good.